Influence of perceived innovativeness, customer perceived values and attitude towards customer value co-creation behaviour in dessert cafés - Ling, Esther Sii Wei (2023)
Dessert cafés are becoming increasingly popular as people embrace the new trend of enjoying after-meal treats. Dessert café owners and managers have been searching for ways of gaining a competitive differentiation to thrive in the fierce competition brought on by rival local shops and well-established international dessert chains. The present study highlights customer perceived innovativeness and its influence on customer perceived values, attitudes, and value co-creation, which can lead to unique experiences that meet customer needs and preferences and provide a competitive advantage. By understanding the mechanism of the customer value co-creation process, dessert café practitioners can gain insight into customer perceptions and encourage more value co-creation activities. Building on the value-attitude-behaviour model, service-dominant logic, and equity theory, the interrelationships of customer perceived innovativeness, three-dimensional customer perceived value, customer attitude, and customer value co-creation behaviour were investigated. This study determined the contribution of first-order innovativeness dimensions, namely menu, technology-based service, experiential, and promotional, to the second-order customer perceived innovativeness construct. Moreover, the mediating effects of perceived values and attitude on the relationship between perceived innovativeness and value co-creation behaviour were examined. Selfadministered questionnaires were distributed online to dessert café customers who have visited and are familiar with one of Malaysia’s twelve dessert café brands. A total of 378 valid responses were used for data analysis. By using the partial least squares structural equation modeling (PLS-SEM) technique, the findings revealed that menu innovativeness is the highest contributor to the second-order customer perceived innovativeness, followed by experiential innovativeness. The findings demonstrated that customer perceived innovativeness was significantly related to perceived values, attitude, and value co-creation behaviour. In addition, functional value acted as a complementary mediator between perceived innovativeness and value co-creation behaviour. Attitude complementarily mediated customer perceived innovativeness and value co-creation behaviour, and fully mediated between emotional value and value co-creation behaviour. Finally, emotional value and attitude worked as a serial mediator between perceived innovativeness and value co-creation behaviour. This study advanced theoretical knowledge on the significant role of perceived innovativeness in increasing perceived values, inducing a positive attitude, and eventually intensifying value co-creation behaviour. The findings provide guidance to dessert café practitioners for improving their innovativeness, emphasizing emotional value and attitude, which can enhance customers' willingness to co-create value.